Optimal Synthesis of Pose Repeatability for a Collaborative Robot - Xu Liu; Song Wang; Aihua Liu; Mingwei Hu (Jixie chuandong)
With the requirement of pose repeatability of robots， searching the optimal arrangement scheme of random motion accuracy of joints can make robot design more reasonable and reduce the development cost of robots. Firstly， based on the analysis of pose repeatability of robots， a mathematical model of pose repeatability is established. The model includes position repeatability and orientation repeatability of robots. Then， with the accuracy optimization evaluation function of maximization of joint motion error， the optimal synthesis of pose repeatability for collaborative robot KUKA iiwa 7 is performed. And the optimal arrangement scheme of random motion accuracy of joints can be obtained. Finally， the method is verified by carrying the pose repeatability test of KUKA iiwa 7， and the results of accuracy design by this method can make robot design more reasonable.